2019
DOI: 10.1007/s10488-019-00956-9
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Recovery Educational Interventions for Mental Health Professionals

Abstract: The history of mental health care has been marked by various struggles in maintaining the dignity of service users. Some reform movements have started to use educational strategies aimed at the beliefs and attitudes of professionals, as well as changing the way that practice is carried out. This paper intends to systematically review and synthesize studies assessing awareness and training activities for mental health professionals covering aspects related to recovery, empowerment, and in general, rightsbased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 87 publications
3
19
0
Order By: Relevance
“…To date, systematic reviews in mental health recovery have focused on conceptualizing personal recovery [ 25 , 29 , 54 60 ], measurement instruments [ 28 , 61 , 62 ], conceptualizing recovery-oriented practice [ 63 ], and intervention effectiveness [ 64 66 ]. One review described what influences the implementation of peer support work specifically [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, systematic reviews in mental health recovery have focused on conceptualizing personal recovery [ 25 , 29 , 54 60 ], measurement instruments [ 28 , 61 , 62 ], conceptualizing recovery-oriented practice [ 63 ], and intervention effectiveness [ 64 66 ]. One review described what influences the implementation of peer support work specifically [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the growing recognition of the limitations of recovery education that is decoupled from practice (Crowther et al . 2019; Eiroa‐Orosa & García‐Mieres 2019) and research indicating that there continues to be a tension between policies that espouse recovery and the lived realities of people using mental health services (Slade et al . 2008), finding workable solutions to enhance the development of recovery‐oriented mental health spaces remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic reviews have identified challenges with education approaches that are decoupled from the every‐day practice within the mental health services. Following a systematic review of recovery education, Eiroa‐Orosa and García‐Mieres (2019) concluded that while education activities made a moderate impact on the beliefs and attitudes of mental health professionals, the impact on practice was less evident. The authors of this review also suggest that although organizations were allocating funds to education, they prevented change by not providing real and tangible support for changes to be implemented and sustained within practice (Eiroa‐Orosa & García‐Mieres 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2017; Warner 2010). They used recovery‐focused educational programmes (RFEPs) as a vehicle for knowledge, attitude, and behavioural change among healthcare providers towards a recovery orientation (Eiroa‐Orosa & García‐Mieres, 2019; Jackson‐Blott et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery‐focused educational programmes (RFEPs) attempted to facilitate a cultural change through educating healthcare providers about the concept of recovery, its principles, and the evidence that support it with the participation of LEPs and consumer researchers (Eiroa‐Orosa & García‐Mieres 2019; Jackson‐Blott et al . 2019).…”
Section: Introductionmentioning
confidence: 99%